Učinkovitost zatiranja invazivne tujerodne vrste navadne barvilnice - Smolnikar, Peter (Gozdarski vestnik, 2024)
Invasive alien plant species (IAPS) are causing many changes in biocenoses around the world. Many methods are known to control IAPS. The suitability of the method and its success depends on each individual case – the main goal that is to be achieved by suppression. In the study, we observed the suppression of American pokeweed plants as part of silvicultural interventions in young forests by cutting American pokeweed at ground level. The objectives of the study were to determine the time spent per area (hectare) and to gain knowledge about the combination of silvicultural weed control and IAPS suppression (eradication). On average, labourers spent 18.8 hours of productive time managing one hectare. The non-productive time factor was calculated using our collected data based on an eight-hour shift day with a 30-minute lunch break. The calculated factor for unproductive time is 1.39 (? = 0.053), which is below the nationally recognised and approved value (1.58) for timber harvesting. Caution is required when interpreting these results, as the factors for unproductive time are often underestimated in short-term studies. The theoretical calculation, which is based on a linear regression of the data, shows that a total of around 22 hours of labour are needed to manage one hectare. Despite the already low non-productive time factor, there is still room for optimising the work process, but this requires long-term time studies.
Keywords: časovna študija; eradication; forestry; gozdarstvo; invasive alien species; invazivne rastline; nega pomladka; Phytolacca americana; silviculture intervention; time study; zatiranje